Medium sebagai Rezim Epistemik: Genealogi Wacana Literasi Keuangan dari Poor Richard's Almanack ke Platform Fintech Indonesia - M. Hidayat (Danudirja Setyabudi Nusantara, 2026)
This study traces the transformation of financial literacy discourse by positioning communication media as the primary unit of analysis. Unlike mainstream studies that view financial literacy as an individual cognitive competence, this research argues that communication media do not merely convey knowledge but also construct economic subjects within power-knowledge relations. Using a critical qualitative approach, this study integrates Fairclough’s three-dimensional critical discourse analysis with Foucauldian genealogy. The data corpus comprises three categories: historical documents (Poor Richard’s Almanac 1733–1758); global and domestic institutional documents (OECD, Presidential Regulations, OJK, SNLIK); and the interfaces of Indonesian fintech platforms (DANA, OVO, Jenius, Bibit, GoPay, ShopeePay, LinkAja, Ajaib). The findings reveal three discursive formations exhibiting lexical convergence: the almanac phase produces economic-moral subjects (industry, frugality, prudence); the institutional phase produces rational-calculative subjects (knowledge-attitude-behavior); and the digital phase produces financialised subjects through gamification, algorithmic paternalism, and the reduction of cognitive friction. This research also reveals that Franklin’s famous quote, “A penny saved is a penny earned,” is apocryphal and a historical distortion that actually reinforces the research thesis. The contribution of this study is not merely to reiterate the critical perspective on financialization but to apply it genealogically to the almanac–institutional–digital trajectory within the empirical context of Indonesia, whilst mapping the lexical convergence that encodes the Calvinist-Protestant ethos as a cross-medium and cross-temporal universal.